KEMAMPUAN PEMECAHAN MASALAH SISWA BERDASARKAN TEORI JOHN DEWEY PADA MATERI TRIGONOMETRI - Rianto, Vina Muthmainna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aims to describe students’ problem solving ability on trigonometry. The research method that used is descriptive with case study. The subject of this research are six students of grade XI MIPA 1 MAN 2 Pontianak that consist of two students in up-group who have high ability of problem solving, two students in mid-group who have medium ability of problem solving, and the last two students in bottom-group who have low ability of problem solving. The data collection instrument that used are written test in essay and unstructured interview guides. The result of analysis data about problem solving ability based on John Dewey’s Theory showed that the students in up-group have high problem solving ability, the students in mid-group have medium problem solving ability, and the students in bottom-grade have medium problem solving ability. Based on this research we can conclude that student’s problem solving ability based on John Dewey’s Theory belong to medium category. Keyword: Problem Solving Ability, John Dewey’s Theory, Trigonometry